A high Gas6 level in plasma predicts venous thromboembolism recurrence, major bleeding and mortality in the elderly: a prospective multicenter cohort study. (8th February 2019) - Schnegg‐Kaufmann, Annatina; Calzavarini, Sara; Limacher, Andreas; Mean, Marie; Righini, Marc; Staub, Daniel; Beer, Juerg‐Hans; Frauchiger, Beat; Osterwalder, Joseph; Kucher, Nils; Matter, Christian M.; Husmann, Marc; et al.
Abstract : Essentials Predictive ability of pro‐hemostatic Gas6 for recurrent venous thromboembolism (VTE) is unknown. We measured Gas6 levels in 864 patients with VTE over 3 years. High Gas6 (> 157%) at diagnosis is associated with VTE recurrence, major bleeding and mortality. Gas6 plasma levels measured 12 months after the index VTE are discriminatory for VTE recurrence. Summary: Background: Growth arrest‐specific gene 6 (Gas6) is a prohemostatic protein with an unknown predictive ability for recurrent venous thromboembolism (VTE). In the elderly, VTE results in higher mortality but does not have a higher rate of recurrence than in younger patients. Consequently, anticoagulation management in the elderly is challenging. Objective: To prospectively investigate the performance of Gas6 in predicting VTE recurrence, major bleeding and mortality in the elderly. Methods: Consecutive patients aged ≥ 65 years with acute VTE were followed for a period of 3 years. Primary outcomes were symptomatic VTE recurrence, major bleeding, and mortality. Plasma Gas6 was measured with ELISA. Results: Gas6 levels were measured in 864 patients at the time of the index VTE (T1) and, in 70% of them, also 12 months later (T2). The Gas6 level at T1 was discriminatory for VTE recurrence ( C ‐statistic, 0.56; 95% confidence interval [CI] 0.51–0.62), major bleeding (0.60, 95% CI 0.55–0.65) and mortality (0.69, 95% CI 0.65–0.73) up to 36 months. VTE recurrence up to 24 months after T2 was discriminated by the Gas6 level at T2 (0.62, 95% CI 0.54–0.71). High Gas6 levels (> 157%) and continuous Gas6 levels at T1 were associated with VTE recurrence up to 6 months and 12 months, respectively. Conclusions: In elderly patients, a high Gas6 level is associated with higher risks of VTE recurrence, major bleeding, and death. These findings support further studies to assess the performance of Gas6 in adjusting the length of anticoagulation.